Padrão alimentar de crianças nascidas com microcefalia no Estado do Ceará - Nóbrega, Nívea Rafaela (2018)
Introduction: Children born with microcephaly need specific attention and care, as they present a setback in neuropsychomotor development, which may lead to impairment in their nutrition, from the initial period of breastfeeding to complementary feeding, which may lead to unfavorable development and growth. In the second half of 2015, a large number of new cases of infants with microcephaly occurred, a fact aggravated by the suspicion of association with the Zika virus. In November of the same year, the Ministry of Health confirmed the relationship between Zika virus infection and the occurrence of microcephaly. To date, there are no studies that show who are these women who have children born with microcephaly and the food pattern of these children. Objective: To know the nutritional practices and the food pattern of children with microcephaly in the state of Ceará. Methodology: This is a cross-sectional study with a convenience sample. We interviewed 83 mothers of children with microcephaly in the state of Ceará. It was carried out in Fortaleza in residences, at the Primary Health Care Units (UAPS), and the Early Stimulation Unit of the Polyclinics of Sobral, Limoeiro, Baturité, Caucaia, Acaraú, Icó, Campos Sales, Quixadá and Juazeiro do Norte. The developed questionnaire was applied by the researcher and professionals involved in the monitoring of the child from June to December 2017. Data were analyzed using descriptive statistics techniques. Results: It was observed that 62.65% of the children had mixed breastfeeding or lacked breastfeeding, 51.28% choked when feeding, 81, 93% had a pasty food consistency, 81.93% used a bottle, 73.53% altered the bottle hole and 51.81% used pacifiers. Conclusion: The study found that the children present difficulty in feeding, important nutritional deviations, such as low weight and risk of overweight, choking, low percentage of breastfeeding. In view of this scenario, it is necessary to follow up with speech therapists and nutritionists to improve oral motor functions and nutritional conditions, and consequently to promote the health and quality of life of children and families. Continuous research is advocated in all manifestations of the syndrome and the general clinical development of children.